Video-based Intervention to Reduce Treatment and Outcome Disparities in Adults Living with Stroke or Transient Ischemic Attack (VIRTUAL): protocol for a randomized controlled trial - Munachi Okpala; Chigozirim Izeogu; Mengxi Wang; Charles Green; Gabretta Cooksey; Thuy Nguyen; Sarah Cohen; Latonya Bryant; Daphne C. Hernandez; Elmer V. Bernstam; Michael Gonzales; Rhonda Conyers; et al. (Trials)
Abstract Background Racial and ethnic disparities in post-stroke blood pressure (BP) control persist, and effective interventions to address post-stroke care inequities are needed. We designed a randomized comparative effectiveness trial to evaluate the Video-based Intervention to Reduce Treatment and Outcome Disparities in Adults Living with Stroke or Transient Ischemic Attack (VIRTUAL) model of care for post-stroke BP reduction. Methods The study will enroll 534 stroke survivors in a randomized trial to receive either the VIRTUAL intervention or enhanced standard care. Individuals with ischemic stroke, hemorrhagic stroke, or transient ischemic attack (TIA) are enrolled before hospital discharge and randomized (1:1) to VIRTUAL or ESC for their post-stroke care. The VIRTUAL care model is a social risk-informed telehealth intervention that incorporates remote BP monitoring and multidisciplinary clinical care from a clinical provider, pharmacist, and social worker. Telehealth (TH) based clinical visits occur 7, 30, 90, and 150 days after hospital discharge with the multidisciplinary care team. Pharmacists monitor and manage BP between telehealth visits for 6 months after enrollment. Patients randomized to ESC receive standard post-stroke follow-up, a BP monitor (without remote capabilities), and pharmacist-engaged care (monthly calls and communication to primary care). The primary outcome is BP control (< 125/75 mmHg) assessed with 24-h ambulatory BP monitoring (ABPM) 6 months after hospital discharge. The secondary outcomes are 24-h ABPM-assessed BP control (< 125/75 mmHg) at 12 months, 6- and 12-month mean systolic and diastolic ambulatory BP, 12-month composite recurrent vascular events, insurance coverage at 3 and 6 months, hospital readmission rates, and acute healthcare utilization (emergency room and urgent care visits) at 3, 6, and 12 months after hospital discharge. Discussion The VIRTUAL care model represents a novel approach to addressing post-stroke BP control disparities. The intervention aims to improve BP control and reduce disparities in a diverse patient population by integrating telehealth with a multidisciplinary team approach and social risk-informed care. Findings from this study will inform evidence-based strategies for enhancing post-stroke care delivery, particularly in underserved populations, and may contribute to reducing healthcare disparities among racial and ethnic groups. Trial registration ClinicalTrials.gov. NCT05264298. Registered on March 3, 2022. URL of trial registry record: https://clinicaltrials.gov/study/NCT05264298?cond=stroke&term=virtual%20&rank=2 . Trial status Protocol version 1.5, approved May 15, 2024. Recruitment started on March 29, 2022, and was completed on April 28, 2025.